2004
DOI: 10.1111/j.1442-2042.2004.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Carcinosarcoma of the bladder diverticulum and a review of the literature

Abstract: We report a carcinosarcoma within a bladder diverticulum together with a review of 18 previously reported cases of intradiverticular sarcomas and carcinosarcomas with respect to their clinical features, treatments and outcomes. Frequent deaths with intra-abdominal recurrences suggest the need for total cystectomy, rather than diverticulectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…rEfErENcEs are characterized by early transmural invasion and have a tendency for higher histopathological grades [4]. Cheng et al corroborated this result and indicated that neoplasms originating in a bladder diverticulum are characterized by a high incidence of local recurrence [5]. Lack of muscle fibers in the diverticulum makes it difficult to stage the tumor.…”
Section: Resultsmentioning
confidence: 64%
“…rEfErENcEs are characterized by early transmural invasion and have a tendency for higher histopathological grades [4]. Cheng et al corroborated this result and indicated that neoplasms originating in a bladder diverticulum are characterized by a high incidence of local recurrence [5]. Lack of muscle fibers in the diverticulum makes it difficult to stage the tumor.…”
Section: Resultsmentioning
confidence: 64%
“…Our patient presented with painless gross hematuria and urinary retention, which are usually the presenting symptoms of the neoplastic changes in bladder urothelium. 4,5 The incidence of neoplastic changes within the bladder diverticulum is estimated at 2% to 10%. 6 There is still no clear pathophysiologic explanation behind these neoplastic changes.…”
Section: Discussionmentioning
confidence: 99%
“…4 Due to its rarity and lack of systematic clinical studies, there are currently no available guidelines regarding the management of neoplasms arising from intravesical diverticulum. With malignant neoplasms confined to the diverticulum, there is better prognosis than those with extravesical extension.…”
Section: Discussionmentioning
confidence: 99%
“…have also been described. [1,2,4] Bladder tumours are more common in men, the incidence increasing with age. [5] Local endoscopic transurethral resection and intravesical instillation of adjuvant chemotherapeutic agents/Bacillus Calmette-Guérin, an immune-modulating agent, are employed for superficial lesions.…”
Section: Discussionmentioning
confidence: 99%